Mathematics Anxiety and Self-Efficacy of Mexican Engineering Students: Is There Gender Gap? - Gustavo Morán-Soto; Omar Israel González-Peña (MDPI AG, 2022)
Studies have reported that there is a gender disparity wherein women do not study equally to men in bachelor's degrees in science, technology, engineering, and math (STEM) areas, although they lead the race of having a better terminal efficiency rate in higher education. This research explores engineering students' math anxiety and math self-efficacy levels, aiming to determine if there is a gender gap for this specific population. Data were collected from 498 students using adapted items from existing surveys. These items were translated to Spanish, and validity tests were used to establish content validity and reliability. A multivariate analysis of variance (MANOVA) was used to determine possible differences between male and female math anxiety and math self-efficacy levels. Male engineering students reported higher self-efficacy and lower math anxiety levels, and this difference was shown to be significant according to the MANOVA results. Findings of this research could help engineering educators to better understand how their students feel when they are practicing and performing math-related activities and what type of strategies could be designed when aiming to ameliorate female students' math anxiety feelings.